Answer: first option
Explanation:
You must apply the Pythagorean theorem:
![s=\sqrt{b^(2)+c^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/16wih2xget1xs1l1mmqslt3nqe5hn8hayz.png)
Where s is the hypotenuse or, in this case the slant height, and b and c are the other legs.
Therefore you can see in the figure that:
b=5m and c=12m
Then the slant height of the cone is the shown below:
![s=\sqrt{(5m)^(2)+(12m)^(2)}=13m](https://img.qammunity.org/2020/formulas/mathematics/middle-school/trm1hgswge5tirlh0mnn0vfp45gspw0crj.png)